Hubungan Riwayat Menonton Media Dewasa, Teman Menonton Media Dewasa dan Perilaku Seksual dengan Kejadian Menarche - Mugawati Aisya; Arief Wibowo (Universitas Airlangga, 2016)
Menarche is an indicator of teenage girls enter puberty phace. Currently the age of menarche is early has decreased every year. It is triggered by the improvement of living standard which is causing the age of menarche to reduce. This research was intended to identify the age of menarche and the lifestyle which lead to menarche. This research an observational research with analytic and descriptive design. Researcher used the questioner to obtain the respondents data. The subjects of this research were the students of grade X in SMA Negeri 1 Driyorejo which already experiencing menarche. The researched variables were the age of menarche, behavior factor and environment factor that aff ect the menarche. The result of this research showed that most of the respondents experiencing menarche at the age of 12 years old. Most of respondents never have sexual imagination but they watch porn movie with their friends sometimes. The respondents mostly ever did sexual behavior before menarche. The conclusion most of the respondents are living unhealthy lifestyle but most of them has a normal menarche. Counseling about healthy lifestyle and parent guide are needed to form healthy lifestyle for teenage girls.